The Effect off Emotional Support, Instrumental Support, and Transformational Leadership on Generation Z Employee Performance at PT X, Kuningan Regency - Febrianti, Sofi; Sabila; Rosmiati , Alya Dwi; Salsabilah, Jihan Siva; Novandi, Dendy (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Employee performance is a critical determinant of organizational effectiveness, particularly among Generation Z employees who exhibit distinctive work values, expectations, and motivational drivers compared to earlier cohorts. This study investigates the effects of emotional support, instrumental support, and transformational leadership on the performance of Generation Z employees at PT X in Kuningan Regency. Data were collected through a structured questionnaire administered to 51 Generation Z employees selected using purposive sampling within a non-probability sampling framework. The data were analyzed using multiple linear regression, preceded by validity and reliability assessments to ensure measurement robustness. The findings reveal that emotional support and transformational leadership exert positive and significant effects on Generation Z employee performance, whereas instrumental support does not demonstrate a significant influence. These results indicate that psychological and relational factors, particularly supportive interpersonal interactions and inspirational leadership behaviors, play a more substantial role in enhancing Generation Z performance than tangible or material-based assistance. This study contributes to the growing literature on Generation Z workforce management by emphasizing the importance of socio-emotional resources and transformational leadership practices in optimizing employee performance within contemporary organizational contexts.